Redesigning a Serious Game App with LESLLA Teachers for Adult Migrant Second Language and Literacy Learners: Enhancing Accessibility and Usability - Malessa, Eva (Germany, 2025)
The lack of adequate digital learning material is a contentious issue in adult migrant literacy education. This study focused on enhancing a serious game’s accessibility and usability for adult second language users with emergent literacy. Using a participatory design approach, teachers redesigned the Lukukupla literacy support app, developed for Finnish-speaking children, elaborating on potential barriers and redesign suggestions in game diaries and interviews. Motor skill and visibility were identified as crucial non-game-specific issues. Game-specific issues, including trauma insensitivity, were identified in learning content, instructions, feedback, visual and auditory input. Teachers’ suggestions emphasized customization and vocabulary training to make the game more relevant and comprehensible for adults. These results highlight how digital learning environments are not automatically suitable for all literacy learners but need to be (re)designed to meet learners’ needs. The article presents recommendations for the development of digital, target-group-specific learning environments for adult learners with limited formal education.